ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK UMUM SYARIAH DI INDONESIA DENGAN METODE CAMELS - admin, INDRIA ISTIAWATI B11110051 B11110051 (Jurnal Manajemen Update, 2015)
The objectives of this research to analyze compare the financial performance between Government Islamic Banks and Private Islamic Banks in Indonesia in the period 2010-2013 by using CAMELSâ€™s ratios. Financial ratios are used consisting of CAR, NPL, NIM, ROA, LDR and MR. The data used in this study were obtained from the Financial Statements of Islamic Bank in 2010-2013, published by each Bank concerned. After passing through the stage purposive sample, the sample is feasible to use as many as 9 samples, 4 Government Islamic Banks (BRI Syariah, Bank Jabar Banten Syariah, BNI Syariah, dan Bank Syariah Mandiri), and 5 Private Islamic Banks (Bank Muamalat Indonesia, Bank Syariah Mega Indonesia, Bank Panin Syariah, Bank Syariah Bukopin, dan BCA Syariah). Analytical techniques used to see comparison of financial performance Government Islamic Banks and Private Islamic Banks is the method of Independent Sample T-Test. The analysis shows that there are not significant differences for each CAMELSâ€™s ratio (CAR, NPL, NIM, ROA, LDR, MR) between Government Islamic Banks and Private Islamic Banks in Indonesia, except for NPL which show there are significant differences Government Islamic Banks has better performance in terms of NPL and NIM ratios, while Private Islamic Banks Has better performance in terms of CAR, ROA, LDR, and MR ratios. Keywords : CAR (Capital Adequacy Ratio), NPL (Non Performing Loan), NIM (Net Interest Margin), ROA (Return On Asset), LDR (Loan Deposit Ratio), MR (Market Risk). Â